2023
DOI: 10.3390/bs13020105
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Clinical Pilates Exercises on Tension-Type Headaches: A Case Series

Abstract: Tension-type-headaches appear as the third most common disease in the general population and have a big impact on quality of life. The aim is to verify the impact of clinical Pilates exercises on pain intensity, impact headaches, neck disability, state of anxiety, depression, stress and quality of sleep in higher-education students. After a sample selection questionnaire was completed, a series of cases was carried out with 9 undergraduate students with tension-type headaches. Five instruments were applied bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…There are studies about the neck suggesting the use of CPE in patients with neck pain and sagittal cervical disorientation, but their number is very small [ 37 ]. Leite et al, in a case series, reported that the clinical Pilates program can induce positive effects on pain intensity, daily life function and negative emotional states related to tension-type headaches [ 22 ]. Studies examining the effect of CPE on headaches are quite limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies about the neck suggesting the use of CPE in patients with neck pain and sagittal cervical disorientation, but their number is very small [ 37 ]. Leite et al, in a case series, reported that the clinical Pilates program can induce positive effects on pain intensity, daily life function and negative emotional states related to tension-type headaches [ 22 ]. Studies examining the effect of CPE on headaches are quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the studies conducted, it is thought that a holistic exercise approach involving the entire spine, such as clinical Pilates, may be more effective in CHA instead of exercises that only concern the cervical region. There is a case series reporting that the Pilates exercise program can induce positive effects on disorders related to tension-type headaches [ 22 ]. However, there are no studies examining the effectiveness of clinical Pilates in CHA.…”
Section: Introductionmentioning
confidence: 99%
“…Only one participant did not show improvement in functional disability attributed to pain in the cervical region. Regarding negative emotional states, six individuals reported improvements, while one individual noted a decline in sleep quality following the program [44].…”
Section: Tension-type Headachementioning
confidence: 99%